Correction to: Boosting Transport Kinetics of Ions and Electrons Simultaneously by Ti3C2Tx (MXene) Addition for Enhanced Electrochromic Performance - Wu, Wenting; Fang, Huajing; Ma, Hailong; Wu, Liangliang; Zhang, Wenqing; Wang, Hong (Nano-Micro Letters, 2021)
Electrochromic technology plays a significant role in energy conservation, while its performance is greatly limited by the transport behavior of ions and electrons. Hence, an electrochromic system with overall excellent performances still need to be explored. Initially motivated by the high ionic and electronic conductivity of transition metal carbide or nitride (MXene), we design a feasible procedure to synthesize the MXene/WO3−x composite electrochromic film. The consequently boosted electrochromic performances prove that the addition of MXene is an effective strategy for simultaneously enhancing electrons and ions transport behavior in electrochromic layer. The MXene/WO3−x electrochromic device exhibits enhanced transmittance modulation and coloration efficiency (60.4%, 69.1 cm2 C−1), higher diffusion coefficient of Li+ and excellent cycling stability (200 cycles) over the pure WO3−x device. Meanwhile, numerical stimulation theoretically explores the mechanism and kinetics of the lithium ion diffusion, and proves the spatial and time distributions of higher Li+ concentration in MXene/WO3−x composite electrochromic layer. Both experiments and theoretical data reveal that the addition of MXene is effective to promote the transport kinetics of ions and electrons simultaneously and thus realizing a high-performance electrochromic device. This work opens new avenues for electrochromic materials design and deepens the study of kinetics mechanism of ion diffusion in electrochromic devices. Highlights: 1 MXene/WO3−x composite film with excellent electrochromic performances was fabricated for the first time. 2 The addition of MXene is an effective strategy for simultaneously enhancing electron and ion transport behaviors in the electrochromic layer. 3 The kinetics of ion diffusion in electrochromic devices are studied in depth based on both experiment and simulation.